A Higher Adherence to the ALINFA Nutritional Intervention Is Effective for Improving Dietary Patterns in Children - Natalia Vázquez-Bolea; Naroa Andueza; Marta Cuervo; Santiago Navas-Carretero (MDPI AG, 2024)
Food patterns are deteriorating and, consequently, not meeting nutritional recommendations. Learning about the adherence to a diet is crucial for understanding children's dietary habits. The objective of the present analysis was to assess the degree of compliance with the ALINFA nutritional intervention and the effectiveness of adherence groups, and to evaluate potential baseline factors predicting a higher adherence to the intervention. A total of 44 children aged 6 to 12 years-old participated in the eight-week intervention. A two-week dietary plan was specifically designed, providing participants with food products, ready-to-eat dishes, and recipes. An intake of 75% of calories of the prescribed diet was defined to divide the participants into high- and low-adherence groups (HA/LA, respectively). From the 44 participants, 24 showed a LA to the intervention, whereas 20 of them were in the HA group. Diet quality improved in both groups (p < 0.001), mainly by increasing cereals and nuts, and reducing pastries. A decrease in BMI z-score was observed (LA: p < 0.001; HA: p = 0.021). Fat mass (p = 0.002), LDL-c (p = 0.036), and CRP (p = 0.023) reductions were only achieved in the HA group, whereas leptin decreased only in the LA group (p = 0.046). All participants ameliorated their dietary habits, but those with better diet quality at baseline experienced greater enhancements in their nutritional status.